Using Geo-Tagged Sentiment to Better Understand Social Interactions - Vivanco, Elizabeth; Palanca, Javier; del Val, Elena; Rebollo, Miguel; Botti, Vicent (Advances in Practical Applications of Cyber-Physical Multi-Agent Systems: The PAAMS Collection, 2017)
Social media have played a relevant role in facilitating communication and coordination among people. Digital traces generated by users in social media sites provides a promising source of data for use in different contexts. The avast amount of data contains information not only about the content of the message but also about who generated the information and to whom it was directed, the instant of time it was published, or the location of the user at the time of publication. Thanks to all this meta-information, the study of users’ actions can be analyzed at different levels of detail and taking into account different perspectives.